2016
DOI: 10.1155/2016/6945415
|View full text |Cite
|
Sign up to set email alerts
|

PET Evidence of the Effect of Donepezil on Cognitive Performance in an Animal Model of Chemobrain

Abstract: A considerable number of patients with breast cancer complain of cognitive impairment after chemotherapy. In this study, we showed that donepezil enhanced memory function and increased brain glucose metabolism in a rat model of cognitive impairment after chemotherapy using behavioral analysis and positron emission tomography (PET). We found that chemotherapy affected spatial learning ability, reference memory, and working memory and that donepezil improved these cognitive impairments. According to PET analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…This initial experiment aimed to study whether donepezil at a relatively high concentration could improve the cognition of normal zebrafish or not. This particular concentration was used based on several prior studies, especially in rats, which found the positive effects of donepezil in a similar concentration on rat cognitive performance [19][20][21][22][23]. As no adverse or beneficial effects on cognitive performance in zebrafish were observed, the adverse effect of donepezil was further examined in other tests.…”
Section: Preparation and Exposure To Donepezil Hclmentioning
confidence: 99%
“…This initial experiment aimed to study whether donepezil at a relatively high concentration could improve the cognition of normal zebrafish or not. This particular concentration was used based on several prior studies, especially in rats, which found the positive effects of donepezil in a similar concentration on rat cognitive performance [19][20][21][22][23]. As no adverse or beneficial effects on cognitive performance in zebrafish were observed, the adverse effect of donepezil was further examined in other tests.…”
Section: Preparation and Exposure To Donepezil Hclmentioning
confidence: 99%
“…These drugs include the selective serotonin reuptake inhibitors (SSRIs) and the acetylcholinesterase inhibitors (tacrine, donepezil, rivastigmine, and galantamine), which have been approved to treat depression and AD, respectively. Donepezil alleviated cognitive problems in two studies of chemobrain (Winocur et al , ; Lim et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Using multiple dimensions in behavioral tasks may more reliably produce frontal cortex dysfunction in rodents (7, 8). Often, operant procedures are used to incorporate multiple dimensions of behavior, however, there are only a few examples in the chemobrain literature (3, 7).…”
Section: 0 Introductionmentioning
confidence: 99%